(untitled) (International Association of Biologicals and Computational Digest, 2022)
Reducing anthropogenic emission of CO2 and other greenhouse gases are important strategies for mitigating the greenhouse effect. Sustainable use of crop residue as a possible source of feedstock should be adequately assessed because of its potential impacts on soil carbon sequestration and good soil quality maintenance. Crop residue plays an important role in climate change mitigation without harming the food security. In the present work, an attempt to evaluate the CO2 emission released from the biomass briquettes compared to that from the coal and their cost benefit analysis has been carried out. The suitability of using biomass briquettes to substitute coal is debatable, as coal gives more production in the industry in less time than briquettes.